Degradation of 17α-ethynylestradiol (EE2) by nitrifying activated sludge containing different ammonia-oxidizing bacterial communities - Panida Sermwaraphan (Chulalongkorn University, 2014)
Thesis (M.Sc.)--Chulalongkorn University, 2006